Nilai Modernitas dan Tradisional dalam Cerpen Pilihan Kompas Edisi 2024: Kajian Sastra Pastoral Gifford - Muhamad Fakhri Ardiansyah; Marisya Listiani; Faranida Aulia Rahmah; Indah Fadhilla (GHANCARAN: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2026)
This study is motivated by environmental issues and ecological awareness in contemporary society, which are never-ending. Literature plays an important role in conveying environmental issues through an ecological lens in works such as short stories, novels, and poetry. This study analyzes several selected short stories from the 2024 edition of Kompas published on the Kompas.id website about environmental damage in a rural area. Through Gifford's pastoral ecocriticism and literary sociology, it is hoped that authors can be assisted in conveying messages expressed through the conflict between traditional values and modernity, as well as their impact on the surrounding ecosystem. The research method used is a descriptive qualitative approach that highlights the concept of pastoral literature in understanding the interaction between humans, nature, and social transformation. The results of the analysis show that several of these short stories present pastoral themes through bucolic elements, Arcadian constructions, idylls, nostalgia, and georgics, as well as discourses of retreat and return, focusing on the beauty of the countryside and traditions that are in harmony with nature. Conflicts arise due to the influence of modernity, such as land exploitation and cultural value shifts that cause ecosystem damage and an identity crisis for local communities. Georgic elements show the community's efforts to preserve their ancestral lands as a symbol of ecological and social sustainability. Several of these short stories successfully represent contemporary environmental issues and invite readers to reflect on the importance of maintaining a balanced relationship between humans and nature.This study is motivated by environmental issues and ecological awareness in contemporary society, which are never-ending. Literature plays an important role in conveying environmental issues through an ecological lens in works such as short stories, novels, and poetry. This study analyzes several selected short stories from the 2024 edition of Kompas published on the Kompas.id website about environmental damage in a rural area. Through Gifford's pastoral ecocriticism and literary sociology, it is hoped that authors can be assisted in conveying messages expressed through the conflict between traditional values and modernity, as well as their impact on the surrounding ecosystem. The research method used is a descriptive qualitative approach that highlights the concept of pastoral literature in understanding the interaction between humans, nature, and social transformation. The results of the analysis show that several of these short stories present pastoral themes through bucolic elements, Arcadian constructions, idylls, nostalgia, and georgics, as well as discourses of retreat and return, focusing on the beauty of the countryside and traditions that are in harmony with nature. Conflicts arise due to the influence of modernity, such as land exploitation and cultural value shifts that cause ecosystem damage and an identity crisis for local communities. Georgic elements show the community's efforts to preserve their ancestral lands as a symbol of ecological and social sustainability. Several of these short stories successfully represent contemporary environmental issues and invite readers to reflect on the importance of maintaining a balanced relationship between humans and nature.